Evidence for an organic origin of pedogenic calcitic nanofibres - Dadras, Massoud; Abolhassani-Dadras, Sousan; Braissant, Olivier; Verrecchia, Eric (My University, 2009)
Calcium carbonate nanofibres are found in numerous terrestrial environments, often associated with needle fibre calcite. This study attempts to mimic the natural system and generate comparable crystalline structures. A comparison of natural and synthesized nanofibre structures, using HRTEM as well as electron energy loss spectroscopy (EELS) and electron spectroscopic imaging (ESI), has demonstrated that this type of nanocrystal can result from precipitation on organic templates, most likely cellulose nanofibres. This study emphasizes the fundamental role of organic templates in the precipitation of calcium carbonate in vadose environments, even at the nanoscale.